Titratable acidity of ripened fresh mangoes (Mangifera indica Linn.) and its relationship to quality of canned mango scoops - Del Rosario, Rosemarie M. (1977)
The study involves the follow-up of the physico-chemical characteristics of mangoes as they ripen and the relation of these with the objective tests and sensory evaluation on the canned mango scoops. Green, mature carabao mangoes were allowed to ripen to four, six and seven days after harvest and then canned as mango scoops. Physico-chemical characteristics of the raw materials and the finished products were evaluated by objective tests. The scoops canned at different degrees of ripeness were also presented to a regular panel for sensory evaluation. Values of T.A. and Bx/TA ratios of the raw materials and of the finished products were found to have significant differences as the mangoes varied in ripeness. Significant differences were also shown for sensory scores on color, sweetness, sourness and general acceptability of the mango scoops as a result of the different degrees of ripeness of the raw materials. Relationships between objective tests and subjective evaluation of the same characteristics of the mango scoops were analyzed. Correlation of the objective tests on raw materials and corresponding tests on the finished products were likewise tested for significance. Finally, titratable acidity of the fresh mangoes were tested for significant correlation with the quality attributes of the mango scoops. Regression analysis and graphs were used to illustrate the relationships better. Percent soluble solids and T.A. were found to have significant correlation with sweetness and sourness, respectively, of the canned mango scoops. Significant correlation coefficients were also obtained between T.A. of the fresh mangoes and that of the finished product and for Bx/TA of the fresh mangoes and that of the finished product. Titratable acidity of the fresh mangoes was found to be significantly correlated with panel evaluation of color, sweetness, sourness of the canned product. Thus it is possible to use this objective test on the raw material to assess the degree of ripeness of the fresh mangoes and predict more or less the quality of the canned mango scoops.
Appendices: leaves 58-96.
Chiefly tables.
Thesis (BSFT)--University of the Philippines, Quezon City.
Typescript.
Keywords: Mango; Food, Canned